Exploring Anonymous Marking to Mitigate Marking Bias: A Self-Study Through Mixed Methods Action Research - Chan, Len (The Canadian Journal of Action Research)

(untitled) (Canadian Association of Action Research in Education, 2025)
Anonymous marking, as a means to mitigate bias in grading, involves evaluating student work with their identities withheld. Anonymous marking is explored in this self-study to mitigate implicit bias, which negated a practitioner-researcher’s educational values. The mixed methods action research findings show withholding student identities during grading alleviates confirmation bias and the halo effect. Despite a short period of adjustment, anonymous marking promotes objectivity and fosters more consistent feedback. However, it prevents personalized feedback, jeopardizes relationship building, and undermines the detection of contract cheating. Moreover, anonymity cannot avert affectual influences and is impracticable for scaffolded formative assessments requiring follow-up feedback. Overall, anonymous marking is shown to be but one measure to counter assessment bias; strategies to mitigate bias unrelated to student identities need to be explored. This self-study also helped the author better understand her role as a practitioner and researcher, enabling her to generate her living-theory.